Analisis Potensi Lingkungan Familia di Stasi Santo Ignatius Pala Pulau Paroki Hati Santa Perawan Maria Tak Bernoda Putussibau Keuskupan Sintang Sebagai Komunitas Basis Gerejawi (KBG) - Angella Dessy Pebriani; Angga Satya Bhakti; Theresia Yovita Cendana Sari (Jurnal Penelitian Pendidikan Agama Katolik, 2024)
As a communion of believers, the Catholic Church uses a variety of faith-enhancing strategies to uphold the beliefs of its members. One of those efforts is developing a local ecclesial lifestyle calledBasic Ecclesial Community. The Sintang Diocese employs the term “Lingkungan” (English: neighborhood) or "Kring" to foster faith at the local level. The “Lingkungan” and Basic Ecclesial Community have unique traits or indicators regarding their comprehension and application. This study aimed to determine whether the “Lingkungan” may develop into a Basic Ecclesial Community. The intention was to gain more recognition for the Basic Ecclesial Community as a fresh approach to spiritual development, particularly for the people who live in the Lingkungan Familia, Santo Ignatius Pala Island, Hati Santa Perawan Maria Tak Bernoda Parish, the Diocese of Sintang. The research method is descriptive-qualitative. This research uses observations and interviews as data sources. The subject is ten credible informants. Utilizing the theories from encyclical documents and scientific references, this research concludes that with all its potencies, Lingkungan Familia could flourish more by developing Basic Ecclesial Communities.